Liberalizing the Malaysian Stock Market - Fathin Faizah Said; Mustazar Mansur; Zulkefli Abdul Karim (Economic Journal of Emerging Markets, 2007)
This paper tries to examine the effect of the volatility that might arises as a result of capital flows according to market opening prior to December 1985 Malaysia case. There-fore, many economists and policy makers concern about the risks associated with the open-ing and globalizing of the markets. Our findings show that stock return becomes less volatile, implying lower return offered to the investors. On the other hand, we proved that globaliza-tion do not reveal any risk to the inflation rate. In contrast, currency return becomes riskier after globalization. Ultimately, we conclude that integrated or liberalized capital flows will affect national policy in stabilizing the domestic economics.JEL Classifications: C22, G12, G18.Keywords: Liberalization, capital market, volatility, Univariate Grach-M.